GENDER DYSPHORIA: GENETIC, EPIGENETIC, AND NEUROBIOLOGICAL BASES OF SEXUAL IDENTITY - Vargas-Vera, Ramón Miguel; Placencia-Ibadango, Martha Verónica; Castro, Paul Vílchez; Salazar, César William Luciano; Hidalgo, Andrea Jimena Tipán; Vargas-Silva, Kalid Stefano; Mejía, Melanie Nicole Lino; Minaya-Becerra, Lady Shirley; Burbano, Moisés Esteven Zambrano; Silva, Karen Soraya Vargas (Seven Editora, 2025)
Gender dysphoria is a condition characterized by a profound incongruence between biological sex and gender identity, which may cause significant distress. Over recent decades, advances in genomics, neurobiology, and epigenetics have enabled the identification of multiple biological mechanisms involved in the determination of sexual identity. Current evidence suggests that gender dysphoria does not stem from a single cause, but rather from the interaction of genetic, endocrine, and environmental factors that modulate sexual differentiation of the brain. Polymorphisms in genes related to hormonal action, such as SRY, SOX9, AR, ERα, SRD5A2, and SULT2A1, may influence brain masculinization or feminization during fetal development. Likewise, neuroimaging studies reveal intermediate or mixed structural and functional brain patterns between cisgender men and women. Epigenetics emerges as an explanatory bridge between genetic and environmental factors through mechanisms of DNA methylation and histone modification. Understanding the biological basis of gender dysphoria is essential for comprehensive clinical care and for reducing social stigma.DOI: https://doi.org/10.56238/sevened2025.036-138